Model Persediaan Multi Item dengan Mempertimbangkan Faktor Kedaluwarsa dan Faktor All Unit Discount - Taufik Limansyah; Dharma Lesmono (Institute of Research and Community Outreach - Petra Christian University, 2011)
This paper deals with determination of ordering policy for perishable goods, namely joint order policy or individual order policy. Expiration date is an important factor to be considered in the inventory system, especially in chemical or food industry. The problem becomes more complicated when the company has more goods with different expired dates. Another factor that has an influence to the inventory system is the supplier discount factor. A company can get benefit from this factor in order to reduce a total cost of inventory. In this paper, performance’s criteria used for the selected policy is ordering policy that minimize the total cost of inventory by considering the expiration date and all unit discount.